A Rare Finding In The Hand Irrigation - Arquez, Humberto Ferreira (Bangladesh Journal of Medical Science, 2018)
Background: The blood supply of the hand is complex and challenging. Awareness of the anatomical variationis necessary not only for the anatomist but also for surgeons.The ulnar artery provides a major blood supply to the hand with the assistance of the radial artery in the form of the superficial palmar arch.The objective of this study was reported a rareanatomical variation of the superficial palmar arch. Materials and Methods: The anatomical variation described was found during routine dissection performed by medical students of second semester in a 75-year-old male embalbed adult cadaver in the laboratory of Morphology of the University of Pamplona. Results and Discussion: In the right hand, the superficial palmar arch only gave rise to two common palmar digital arteries. In the left hand, the arch provided common palmar digital arteries which ran into the first, third and the fourth spaces and one proper palmar digital for the little finger. The arch does not supply the second intermetacarpal space. Conclusions: Less critical knowledge of vasculature of the hand might lead iatrogenic injury during surgery, microvascular surgery for revascularization, replantation and composite tissue transfers. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.496-500